Fostering Critical Thinking Skills In Elementary Schools With Video-Assisted Discovery Learning - Iskandar, Nurul Anissa; Krismanto, Wawan; Lukman, Lukman (Journal of Classroom Action Research, 2024)
This study aims to examine the implementation of video-assisted discovery learning to improve the critical thinking skills of elementary school students. The approach is qualitative to the type of classroom action research. The research subjects were 20 students and 1 teacher at fourth-grade Public Elementary School 35 Pammanu, Luwu Regency, South Sulawesi, Indonesia. The approach is qualitative with the type of classroom action research (CAR). This research was carried out in two cycles on sains with force and motion material. Each cycle is completed in two learning meetings. Observation, tests, and documentation obtained data. The data analysis procedures used are condensation, data presentation, and conclusion. The results showed that the learning process using video-assisted discovery learning showed changes in student learning activity and engagement, learning interaction, learning atmosphere, and student learning focus getting better. The category of students' critical thinking skills has increased from 60% of students in the sufficient and very critical categories in Cycle I to 85% in Cycle II. Thus it can be concluded that implementing discovery learning assisted by video media can improve the learning process and students' critical thinking skills in the science learning in fourth-grade Public Elementary School 35 Pammanu, Luwu Regency, South Sulawesi.